Implementasi Teknik Remarketing Menggunakan Tools Google Analytics untuk Melakukan Promosi PMB Tertarget - Yopi Hidayatul Akbar (Universitas Maso'em Bandung, 2021)
Marketing strategy is very important for companies where marketing strategy is a way of achieving the goals of a company, because the potential to sell a proposition is limited to the number of people who see it. With the conventional marketing concept, the target to achieve the goal cannot be maximized, it only eliminates time and cost. With the large number of smartphone users and information technology today, digital marketing techniques will be more efficient, because marketing targets can be managed to only certain segments. The application of remarketing techniques is of course not only done by google analytics, but also Facebook ads to monitor events or user interactions with ads that have reached certain locations. At this time, implementing the remarketing method on Google Analytics and Facebook Ads by utilizing research events and ad conversion so that data that has interacted with ads on Facebook will also enter into tracking data. From the analysis of the results that have been carried out by the author, it can be concluded that online marketing techniques with the application of appropriate remarketing techniques will be able to increase visitor traffic. The evaluation results are expected to be a good solution and recommendations for online promotion so that the results can be targeted as expected.